Pengaruh Tingkat Penambahan Fly Ash terhadap Kinerja Mekanik Beton - Muhamad Syahrul; Sumarman Sumarman; Lutfi Marantica (Jurnal Talenta Sipil, 2026)
The increasing demand for concrete in infrastructure development leads to higher cement consumption, while cement production is a significant source of carbon dioxide emissions. The use of fly ash as a partial cement replacement offers an alternative to produce more efficient and environmentally friendly concrete. This study aims to analyze the effect of fly ash substitution on workability and compressive strength, determine the optimum technical dosage, and evaluate simple cost efficiency. The research employed a laboratory experimental method with fly ash variations of 0%, 10%, and 20% by weight of cement. Tests were conducted on slump and 14-day compressive strength using three cylindrical specimens for each variation. The 28-day compressive strength was estimated based on a 0.73 strength development factor from the 14-day results. The results show that slump decreased from 13.0 cm in normal concrete to 11.0 cm at 10% fly ash and 10.5 cm at 20% fly ash. The average 14-day compressive strengths for 0%, 10%, and 20% variations were 40.481 MPa, 40.953 MPa, and 35.858 MPa, respectively, with estimated 28-day strengths of 55.454 MPa, 56.100 MPa, and 49.120 MPa. The 10% fly ash variation produced the highest compressive strength, increasing by 1.17% compared to normal concrete. Cost analysis indicates savings of 3.60% for 10% fly ash and 7.20% for 20% fly ash. Therefore, 10% fly ash is recommended as the optimum technical proportion, while 20% fly ash is more suitable for cost efficiency but should be applied cautiously in structural applications.